Case report: Magnetic resonance imaging-based three-dimensional printing for reconstruction of complex cloacal malformations - Gang, Suiin; Song, Sang Hoon; Kwon, Jaeyoung; Kwon, Hyunhee; Ha, Suhyeon; Park, Jueun; Kim, Namkug; Yoon, Hee Mang; Namgoong, Jung-Man (Frontiers in Pediatrics, 2023)
Background: Surgical reconstruction of the urinary tract, anus, and vagina is the definitive treatment for cloacal malformation. However, this procedure may be technically challenging in patients with a long common channel (>3 cm), because further reconstructive procedures, such as vaginal replacement or vaginal switch maneuver, may be required. Thus, accurate determination of spatial anatomy is essential during surgical planning. Three-dimensional (3D) reconstruction using rotational fluoroscopy, computed tomography (CT), and magnetic resonance imaging (MRI) has recently been reported to help in determining the relationship between the rectum, vagina, and bladder, and provides a more accurate measurement of the channel length compared to conventional cloacography. MRI-based 3D reconstruction provides substantial information regarding soft tissue structures around the cloaca, including the pelvic floor musculature and anus. Case: A 2-year-old girl with cloacal malformation required reconstructive surgery. Colostomy and cystostomy had been performed on the first day of her life. Preoperative loopogram revealed a cloaca with a long common channel (35 mm) and short urethra (9 mm), single vaginal opening in the bladder neck, and the colon anterior to the vagina with a fistula at the vaginal neck. Because the vagina was too short to be pulled through, 3D printing based on MRI was performed to visualize structural relationships prior to surgical correction. Saline was used for cloacal visualization. Furthermore, endoscopy-assisted urogenital mobilization was performed, and vaginal substitution was performed using the rectum. No postoperative complications were observed. Conclusions: We believe this is the first report of the use of MRI-based 3D imaging and printing, with saline as a contrast agent during surgical planning for correction of cloacal malformation. MRI-based 3D printing is a potentially promising technique for surgical planning of cloacal malformation correction in patients with a long common channel, as it provides detailed information about the surrounding soft tissue structures without exposure to radiation or contrasting agents.